Combination of natural polyanions and polycations based on interfacial complexation for multi-functionalization of wound dressings - Li, Shuyang; Wang, Liya; Zhang, Jue; Zhao, Zijun; Yu, Weifeng; Tan, Zhi; Gao, Po; Chen, Xingtao (Frontiers in Bioengineering and Biotechnology, 2022)
Multi-functionalization of wound dressings with natural polymers is meaningful and remains a challenge. The combination of natural polyanions and polycations appears to be a promising strategy. Still, its performances based on current layer-by-layer self-assembly or homogeneous complexation are mutable and limited. Herein, Ca2+-incorporated carboxymethyl cellulose (Ca/Na-CMC) and hydroxypropyltrimethyl ammonium chloride chitosan (HACC) are adopted as the model polyanion and polycation, respectively, to develop multi-functionalized dressings based on interfacial complexation. The dressings exhibit a multilayer structure composed of a polyanion layer (Ca/Na-CMC) for hemostasis and promotion of cell proliferation, a formed polyelectrolyte complex (PEC) layer for structural stability, and a polycation layer (HACC) for antibiosis. Compared to the dressing based on homogeneous complexation, the multilayer dressings show stronger moisture penetrability (around 1,150 g/m2/24 h), higher hemostatic activity, and higher antibacterial rate (up to 100%) and promoted effect on cell proliferation. An in vivo evaluation using a rat full-thickness skin defect model reveals that the multilayer dressings can accelerate wound healing in 2 weeks. Overall, owing to interfacial complexation resulting in separate layers, the performances of polyanions and polycations after combination are more predictable, and their biological functions can be effectively preserved. These findings not only support the extensive application of multilayer dressings but also offer an alternative strategy for multi-functionalizing wound dressings with natural polyanions and polycations.